Hydrothermally grown nano-WO3 electrochromic film: structural and Raman spectroscopic study. Issue 1 (2nd January 2022) - Chaudhary, Anjali; Pathak, Devesh K.; Tanwar, Manushree; Dash, Rupashree; Joshi, Bipin; Keerthivasan, T.; Kandpal, Suchita; Ghosh, Tanushree; Rani, Chanchal; Kumar, Rajesh
ABSTRACT: Tungsten oxide (WO3 ) thin films have practical implications in a variety of technological fields including electrochromic devices thus a good quality film must be deposited using an appropriate method. This drives the research on fabricating uniform, nano-particle sized WO3 film for application-oriented work. Synthesis of well distributed, porous and uniform nano- WO3 film using single-step hydrothermal synthesis method has been reported here followed by investigation of its electrochromic properties. Structural and spectroscopic studies have been carried out using SEM, XRD and Raman spectroscopy. The SEM results reveal uniform deposition of WO3 nanoparticles all over the substrate. Raman and XRD spectroscopy have been further used to investigate its structural composition. Excellent properties possessed by WO3 film make it standing apart in inorganic materials' realm and open the door for its varied device-oriented applications especially in the field of electrochromism.